Sharka disease: Current status, diagnosis and potential treatments - Özden Çiftçi, Yelda; Gül Şeker, Mine; Gumusel, D.; Elibüyük, Ibrahim Ozer (Nova Science Publishers, Inc., 2012)
Plum pox virus (PPV), the cause of the Sharka disease, is considered to be the most serious virus of stone fruits (Prunus spp.), which is transmitted in a non-persistent manner by several aphid species and vegetative production materials. Following its first determination in plums in Bulgaria, the virus has progressively spread to European continent and the Mediterranean Basin. It has also been sporadically detected in America (Argentina, Chile, Canada and USA) and in Asia (China, India, Iran, Kazakhstan and Pakistan). The diagnosis of the virus can be achieved by indicator plants, serological (i.e., ELISA) and molecular techniques (i.e., RT-PCR, IC-RT-PCR, microarray). However, trees infected with PPV cannot be treated. The practical prevention of the disease involves the production of healthy plants for planting, control of aphid vectors and destruction of infected trees in orchards. Several methods are used for obtaining initial virus-free propagation materials, such as thermotherapy, chemotherapy, electrotherapy, and cryotherapy. Breeding for resistance is the only way to control Sharka efficiently. However, at present very limited tolerant or resistant varieties of Prunus species are exist in the nature. The pathogen-derived resistance has been experimented to control the disease. In view of the crucial importance of Sharka disease, characteristics of the virus and the disease, detection techniques together with the potential applications and benefits of both classical and biotechnological treatments were discussed in this chapter. © 2012 by Nova Science Publishers, Inc. All rights reserved. © 2014 Elsevier B.V., All rights reserved.
Keywords: Control methods; Plum pox potyvirus; Sharka; Virus detection; Virus-free planting material